2014
DOI: 10.1017/jfm.2014.203
|View full text |Cite
|
Sign up to set email alerts
|

Tracking stages of transition in Couette flow analytically

Abstract: The current study focuses on a transition scenario in which the linear transient growth mechanism is initiated by four decaying normal modes. It is shown that the four modes, the initial structure of which corresponds to counter-rotating vortex pairs, are sufficient to capture the transient growth mechanism. More importantly, it is demonstrated that the kinetic energy growth of the initial disturbance is not the key parameter in this transition mechanism. Rather, it is the ability of the transient growth proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…These scaling factors are consistent with the theoretical analysis by Chapman [5]. More recently, Karp et al [6,7] showed that the optimal set of parameters for transition in the pCf is associated with initial disturbances, which generate the strongest inflection point in the mean flow profile when nonlinearities come into play. In the same vein, Cossu et al [8] investigated the streak breakdown in a two-dimensional parameter space with respect to the amplitudes of the low-speed streak and its secondary perturbation.…”
Section: Introductionsupporting
confidence: 82%
“…These scaling factors are consistent with the theoretical analysis by Chapman [5]. More recently, Karp et al [6,7] showed that the optimal set of parameters for transition in the pCf is associated with initial disturbances, which generate the strongest inflection point in the mean flow profile when nonlinearities come into play. In the same vein, Cossu et al [8] investigated the streak breakdown in a two-dimensional parameter space with respect to the amplitudes of the low-speed streak and its secondary perturbation.…”
Section: Introductionsupporting
confidence: 82%
“…In the closely related case of the flow in a square duct, Biau, Soueid & Bottaro (2008) found that the key mechanism for rapid transition is the generation of an unstable mean flow distortion that supports further exponential or algebraic growth. Along a similar train of thought, it was recently shown by Karp & Cohen (2014) that non-modal growth can lead to rapid transition in Couette flow through nonlinear interactions. The authors demonstrated that the key factor to cause a rapid breakdown is the ability of the transient growth process to induce inflexion points in the base state.…”
Section: Discussionmentioning
confidence: 84%
“…In this appendix we describe the linear stability analysis of a base flow, , which is inhomogeneous in two spatial directions (e.g., Karp & Cohen 2014). At given time , we assume the following velocity field: Here the base flow is assumed parallel, steady and streamwise independent, and is the disturbance.…”
Section: Figure 27mentioning
confidence: 99%